1972
DOI: 10.1146/annurev.ph.34.030172.000305
|View full text |Cite
|
Sign up to set email alerts
|

Circulation: Overall Regulation

Abstract: Cerebral Arteriovenous Malformation (CAVM) hemodynamic in disease condition results changes in the flow and pressure level in blood vessels. This can cause rupture or decreased blood supply to the tissue through capillary causing infarct. Measuring flow and pressure without intervention along the vessel is big challenge due to occlusion, bending and thinning of the vessel in Arteriovenous Malformation patients. In this paper, we proposed a lumped model for the Bifurcation for symmetrical and asymmetrical netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
485
0
17

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 782 publications
(507 citation statements)
references
References 61 publications
5
485
0
17
Order By: Relevance
“…There is a long tradition in physiology and biochemistry of building ordinary differential equation (ODE) models of a broad diversity of systems (Guyton et al 1972;Ten Tusscher et al 2004;Keener and Sneyd 2009). One of the challenges in building a model that accurately simulates the properties of a biological system is that we often do not know the entire network that might be relevant, nor all the kinetics that link all the variables.…”
Section: Mathematical Models Of Biological Systemsmentioning
confidence: 99%
“…There is a long tradition in physiology and biochemistry of building ordinary differential equation (ODE) models of a broad diversity of systems (Guyton et al 1972;Ten Tusscher et al 2004;Keener and Sneyd 2009). One of the challenges in building a model that accurately simulates the properties of a biological system is that we often do not know the entire network that might be relevant, nor all the kinetics that link all the variables.…”
Section: Mathematical Models Of Biological Systemsmentioning
confidence: 99%
“…Over thirty years ago, Dr. Arthur Guyton suggested that circulatory physiology was starting to change into and use the techniques of engineering science [1] and his model made large strides towards this change. Unfortunately, his famous circulatory physiology model has not developed significantly since 1992 in the practical form of a block diagram of systems and subsystems.…”
Section: Discussionmentioning
confidence: 99%
“…Since the model size, and number of variables and parameters, has increased immensely since the first version of the model from 1972, multiple layers of subsystems were used. At the lowest level, a first order dynamic system was implemented as in the original model diagram [1] with an integrator, a gain and a summer, as in Fig. 4, and was subsequently 'masked' as a transfer function in the s-domain in the form of:…”
Section: Guyton's Model In Simulinkmentioning
confidence: 99%
See 2 more Smart Citations